Exercise training improves heart rate recovery in women with breast cancer - Giallauria, Francesco (Springerplus, 2015)
PURPOSE: To determine whether exercise training improves autonomic function in women with breast cancer (BC). METHODS: Fifty-one patients (aged between 39 and 72 years) with a history of primary invasive BC within the previous 5 years and enrolled in the Mediterranean diet-based DIANA (Diet and Androgens)-5 Trial were subdivided in two groups: a ET group (n = 25) followed a formal ET program of moderate intensity (3 session/week on a bicycle at 60–70% VO(2peak) for 3 months, followed by one session/week until 1-year follow-up), while a control group (n = 26) did not perform any formal ET. At baseline and after 1-year, all patients underwent cardiopulmonary exercise stress test (CPET). Heart rate recovery (HRR) was calculated as the difference between heart rate at peak exercise and heart rate at first minute of the cool-down period. RESULTS: There were no significant differences between groups in baseline anthropometrical, BC characteristics, metabolic profile, CPET parameters and HRR. Compared to controls, at 1-year follow-up ET group showed a significant improvement in VO(2peak) (from 12.6 ± 3.0 to 14.5 ± 3.3 ml/kg/min, p < 0.001; p < 0.001 between groups); and in HRR (from 17.6 ± 6.4 to 23.0 ± 8.3 beats/min, p < 0.001; p < 0.001 between groups). In ET group the changes in HRR directly correlated with changes in VO(2peak) (r = 0.58, p = 0.002). CONCLUSIONS: Moderate intensity exercise training in BC survivors is associated with improvement of autonomic function. Whether the improvement of sympatho-vagal balance may favorably modulate some of the pathophysiological mechanisms implied in cancer evolution need further investigation.